Proteomics, toxicity and antivenom neutralization of Sri Lankan and Indian Russell’s viper (Daboia russelii) venoms - Faisal,Tasnim (2021)
Abstract Background: The western Russell’s viper (Daboia russelii) is widely distributed in South Asia, and geographical venom variation is anticipated among distant populations. Antivenoms used for Russell’s viper envenomation are, however, raised typically against snakes from Southern India. The present study investigated and compared the venom proteomes of D. russelii from Sri Lanka (DrSL) and India (DrI), the immunorecognition of Indian VINS Polyvalent Antivenom (VPAV) and its efficacy in neutralizing the venom toxicity. Methods: The venoms of DrSL and DrI were decomplexed with C18 high-performance liquid chromatography and SDS-polyacrylamide gel electrophoresis under reducing conditions. The proteins fractionated were identified through nano-ESI-liquid chromatography-tandem mass spectrometry (LCMS/MS). The immunological studies were conducted with enzyme-linked immunosorbent assay. The neutralization of the venom procoagulant effect was evaluated in citrated human plasma. The neutralization of the venom lethality was assessed in vivo in mice adopting the WHO protocol. Results: DrSL and DrI venom proteomes showed comparable major protein families, with phospholipases A2 (PLA2) being the most abundant (> 60% of total venom proteins) and diverse (six protein forms identified). Both venoms were highly procoagulant and lethal (intravenous median lethal dose in mice, LD50 = 0.24 and 0.32 µg/g, for DrSL and DrI, respectively), while lacking hemorrhagic and anticoagulant activities. VPAV was immunoreactive toward DrSL and DrI venoms, indicating conserved protein antigenicity in the venoms. The high molecular weight venom proteins were, however, more effectively immunorecognized than small ones. VPAV was able to neutralize the coagulopathic and lethal effects of the venoms moderately. Conclusion: Considering that a large amount of venom can be injected by Russell’s viper during envenomation, the potency of antivenom can be further improved for optimal neutralization and effective treatment. Region-specific venoms and key toxins may be incorporated into the immunization procedure during antivenom production.